Invariance principle for independent random variables with infinite variance - Juodis, Mindaugas (Lietuvos matematikos rinkinys, 2023)
A functional central limit theorem for self-normalized adaptive process U−1m,N ζn is considered, where Um,N is a sum of squares of block-sums of size m, as m and the number of blocks N = n/m tend to infinity.